Türkiye’ de kamu iç borçlanmasının enflasyonla ilişkisi (1990- 1999) - Özkan, Ahmet Burak (My University, 2000)
EXTRACT For a period of time, internal public loans used to require for an extraordinary issues. Nowadays, it is used by both developed and developing countries as a special financial instrument. Internal loaning, after the year of 1980' s, reached a high level of our public finance. At the Year of 1990, the rate of Internal Loans to the Gross National Product was around 14,3 %, İt reached to 20 % at the year of 1994 and finally it was more than 25 % at the year of 1999. Increasing in internal loans are the primary and also most important factors of the economy as well as this thesis. In part one, public loans and also internal loanings were examined in a technical manner. In part two, subtitels for public loan in Turkey was searched and examined. In addition to this,the instruments of the selling systems and strategy were mentioned. In part three, the evaluation process of loanings for last twenty years were axamined. On the other hand, by the way of statistical methods, from 1990' s till now were searched for the factors of increasing in internal loanings. In part four, the general effects of inflation to the loaning were mentioned for the period of 1990' s till now. Every applications of loaning achieves different results in economy. From the year of 1980' s, Turkish Economy moved to improvement platform therefore, it required much more attention as for the reason and result relations.
Keywords: Borçlanma; ENFLASYON-TÜRKİYE